Mapping the Falkland Islands Dependencies - Leay, Petra (Polar Record, 1956)
Summary It is just ten years since the Directorate of Colonial Surveys became responsible for the production and publication of maps of the Falkland Islands Dependencies; in this account it is proposed to give a description of the work completed and an outline of the future programme. “Operation Tabarin”, inaugurated in 1943, marked the re-establishment of British occupation and scientific activity in the region and included in its policy a programme of continuous scientific investigation within the area between 20° and 80° W. This venture later became known as the Falkland Islands Dependencies Survey, or F.I.D.S. It is in co-operation with F.I.D.S., and more particularly with the surveyors who work at the Directorate for several months on their return from the Antarctic, that the compilation and plotting of a systematic series of medium scale maps has been possible. In 1951 an article was published in this journal giving a full description of the type of survey undertaken, the methods and the instruments used and a brief summary of the maps published and planned. At first the need was for maps for planning and other non-scientific purposes, but since 1951 the emphasis has moved towards the larger scales which are required principally as a basis for scientific work as well as for general use within the Dependencies. Between 1948 and 1950 a series of maps covering most of the area north of 75° S. was published at 1:500,000, and this is still the most useful scale for gaining a general picture of the topography. In 1953 work began on a series of maps covering a similar area to be published at 1:200,000. During the last ten years maps have been compiled at scales ranging from 1:9 million to 1:15,000, many of which have been printed and issued for general purposes, while others have been produced to illustrate specialized reports on, for example, meteorology in the Dependencies. It is not, however, proposed to include a detailed summary of these maps here, the following description covers only those maps which are ...